Impact of antibody Fc engineering on translational pharmacology, and safety: insights from industry case studies - Frank R. Brennan; J. Ryan Polli; Jean Sathish; Melissa Ramones; Babette Wolf; Tilman Schlothauer; Shirley J. Peters; Curtis C. Maier; Changhua Ji; David L. Wensel; Derrick Witcher; Patricia C. Ryan; et al. (mAbs)
Therapeutic monoclonal antibodies (mAbs) are often designed to not only bind targets via their antigen-binding domains (Fabs) but to also engage with cell surface receptors, FcγRs and FcRn, through their Fc regions, which may result in a variety of functional outcomes, including antibody- dependent cellular cytotoxicity (ADCC), antibody-dependent cellular phagocytosis (ADCP), complement-dependent cytotoxicity (CDC) and alteration of circulating half-lives. Engineering the Fc regions to achieve desirable pharmacology and pharmacokinetics is a widely adopted strategy in drug development. Fc regions can be modified through amino acid substitutions and glycoengineering, resulting in enhanced or reduced effector functions, preferential binding to FcR subtypes, or pH-dependent binding to FcRns. These alterations in binding and effector activities of mAbs may potentially also be accompanied by undesirable effects or safety concerns. Critical assessment of pharmacology and safety in the nonclinical setting is essential before exposing humans to the engineered mAb. For Fc-modified mAbs, the choice of in vitro and in vivo nonclinical pharmacology and safety models need to account for species differences in FcR expression and function, potentially divergent effects of Fc modifications in humans versus nonclinical species, impact of target and cognate ligand expression patterns, and potential impact of emergent anti-drug antibodies directed against the mAb. Using a variety of industry case studies, we highlight key aspects of nonclinical pharmacology and toxicology testing strategies, factors that influence choice of nonclinical models, translatability of findings, input from health authorities and suggest best practice approaches for nonclinical testing of Fc modified mAbs.